2014
DOI: 10.5152/tjar.2014.33254
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Sudden Hypotension Due to Relative Adrenal Insufficiency

Abstract: 283Systemic blood pressure is regulated by three mechanisms: the sympathetic nervous system, the renin-angiotensin system, and the arginine-vasopressin system. Hypotension is a condition that can occur at any stage of management of general anaesthesia, including induction, extubation, and maintenance. Many of the medications used for anaesthesia produce a mild to moderate decrease in systemic vascular resistance (SVR) with a subsequent decrease in arterial blood pressure. Profound and sustained hypotension, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Acute adrenal insufficiency or adrenal crisis is a condition of shock resistant to catecholamines, which can occur in those who have been already diagnosed with the condition but have not increased the dose of glucocorticoids, in those without a prior diagnosis or in those who have encountered a great physiological stress. Patients with no known adrenal insufficiency in the past who have insufficient cortisol response to stress with normal serum cortisol are supposed to have relative adrenal insufficiency 9. The most frequent precipitating causes are gastroenteritis and fever (60%–70%), but other stressful events can also cause crises, such as trauma, surgery, a dental procedure, and major psychological distress 10.…”
Section: Discussionmentioning
confidence: 99%
“…Acute adrenal insufficiency or adrenal crisis is a condition of shock resistant to catecholamines, which can occur in those who have been already diagnosed with the condition but have not increased the dose of glucocorticoids, in those without a prior diagnosis or in those who have encountered a great physiological stress. Patients with no known adrenal insufficiency in the past who have insufficient cortisol response to stress with normal serum cortisol are supposed to have relative adrenal insufficiency 9. The most frequent precipitating causes are gastroenteritis and fever (60%–70%), but other stressful events can also cause crises, such as trauma, surgery, a dental procedure, and major psychological distress 10.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol provides cardiovascular stabilization during stress. The need for inotropic support and high doses of inotropic drugs is an indicator of adrenal insufficiency in ICU patients (23)(24)(25). Oboni et al examined the predictive factors of adrenal insufficiency in patients presenting with urgent complaints and found that eosinophilia was associated with adrenal insufficiency, whereas acidosis and CRP elevation were not (26).…”
Section: Discussionmentioning
confidence: 99%
“…Acute adrenal insufficiency or adrenal crisis can develop in patients with adrenal insufficiency or in those who are in steroids therapy but have not increased the dose of glucocorticoids, as well as in patients without a prior diagnosis that have encountered acute physical stress. Adrenocortical insufficiency should be suspected in the event of hypotension in patients with chronic glucorticoid therapy who does not respond to fluid replacement and vasopressor agents [48].…”
Section: Clinical Monitoring Of Perioperative and Postoperative Complmentioning
confidence: 99%